The Effects of The Presence of Tutor in The Learning Video on Cognitive Load and Academic Achievement: Array - Weni Anggraini; Sunawan Sunawan; Ali Murtadho (Islamic Guidance and Counseling Journal, 2020)
This study was intended to determine the effect of the presence of tutors in the learning video on cognitive load and academic achievement. The design used in this study was the posttest control group design. The subjects of this study were 30 students of eleventh-grade science of senior high school number 1 Ungaran. The measurements of the data were carried out using cognitive load questionnaires, eye-tracking measurements, and biological matter of reproductive materials (prior knowledge and posttest teaching). The result of analysis using the Multivariate analysis of variance test showed that the presence of tutors in the learning video did not have a significant effect on extraneous load (F(2.27)=2.6, p>0.05), the presence of tutors in the learning video did not have a significant effect on germane load in the subjective measurements (F(2.27)=0.06, p>0.05), however, the presence of tutors in the learning video has a significant effect on the objective measurements (F(2.27)=24.47, p<0.05) and (F(2.27)=28.14, p<0.05). Furthermore, the presence of tutors in the learning video has a significant effect on academic achievement with (F(2.27)=3.38, p<0.05). The findings of this study proved that there were effects of the presence of tutor in the learning video on germane load and academic achievement.